(untitled) (المجلة الدولية للبحوث العلمية, 2023)
Ionizing radiation is widely used in the field of medicine both for diagnosis and treatment. So, Understanding the principles of radiation safety and how to apply them in clinical practice is critical for medical and paramedical staff The study was conducted to assess the knowledge of nursing staff about ionizing radiation and protection from ionizing radiation during the diagnostic and therapeutic examination. In this study, a quantitative descriptive approach and a comprehensive review of previous studies were followed in order to emphasize the importance of teaching medical physics and ionizing radiation science because of its extremely important impact on the nursing staff working in medical institutions and radiological examination centers of both types, diagnostic and therapeutic. Through this study, we noticed that the paramedical staff’s knowledge of physics and technology was not sufficient, and from our point of view, it does not meet the needs of healthcare institutions that require a deep understanding of tools and equipment that depend on the principles and laws of physics. We also expect that the nursing staff’s lack of knowledge of the physical foundations and laws that are used may have a negative impact on the patients’ condition in clinical practice. Thus, there is a need to improve nursing students’ knowledge of physics by changing the way biophysics is taught in the nursing curriculum.